Applications of Artificial Intelligence Techniques in Engineering SIGMA 2018, Volume 1 - Malik, Hasmat; Srivastava, Smriti; Sood, Yog Raj; Ahmad, Aamir (Advances in Intelligent Systems and Computing,, 2019)
The book is a collection of high-quality, peer-reviewed innovative research papers from the International Conference on Signals, Machines and Automation (SIGMA 2018) held at Netaji Subhas Institute of Technology (NSIT), Delhi, India. The conference offered researchers from academic and industry the opportunity to present their original work and exchange ideas, information, techniques and applications in the field of computational intelligence, artificial intelligence and machine intelligence. The book is divided into two volumes discussing a wide variety of industrial, engineering and scientific applications of the emerging techniques. .